Reasons for discontinuation of contraception among women with a current unintended pregnancy in 36 low and middle-income countries - Bellizzi, S.; Mannava, P.; Nagai, M.; Sobel, H.L. (Contraception (Stoneham), 2020)
To explore the reasons for discontinuation of the last contraceptive method used in women with a current unintended pregnancy. We conducted a retrospective analysis using contraceptive calendar data from Demographic and Health Surveys from 36 low- and middle-income countries from 2005 through 2014. The prevalence of contraception utilization and the contribution of each reason for contraceptive discontinuation was calculated, at country level as well as for the pooled dataset, for 10,901 women aged 15–49 before the current unintended pregnancies. Unintended pregnancies ranged from 5.5% of all pregnancies in the Kyrgyz Republic to 60.0% in Colombia and Peru. In Central Asian and in six African countries, over 80% of women with a current unintended pregnancy had not used any contraceptives in the previous five years. Use of long-acting modern methods remained consistently low across all countries. Among women who last used a traditional method, 83.8% discontinued due to failure. Among women who last used a long-acting modern method, 40.2% discontinued because of side effects. Our findings confirm that more than 65.0% of women with an unintended pregnancy in 36 low and middle-income countries were either non-users or using traditional methods. An additional 31.2% were using short-acting modern methods. Long-acting methods would have prevented the overwhelming majority of unintended pregnancies. This paper shows the need for the health system to support use of suitable methods, reduce switching failure and identify early when women are having concerns about the method they are using.